A chaos-based medical image encryption method - Xuehong Wang; Chunling Tu (Institute of Advanced Engineering and Science, 2020)
The information in the e-health system involves the patient’s privacy which is extremely sensitive. For instance, these information record social security numbers and detailed medical history. When the breach happens, there are illegal, or disclosure behaviors taken to privacy that should be compromised security. In this paper, the medical digital images are protected by the proposed chaos-based encryption method in the process of transmission and utilization. Then the authentication is granted to patients and telemedicine staffs by the decryption method proposed. The Qi 3-D four wing chaotic system is employed in this method. The proposed method promises the keys with higher complexity and unpredictability than traditional cryptography methods by introducing the chaotic dynamics in the new cryptography. Digital medical images are used to validate the proposed method under the brute and the differential attacks. The pixels of the image are scrambled completely based on cat map and the sub-blocks of the image are diffused in the way that the original image is changed into a chaotic image robust to all kinds of attacks. The experiments show that the proposed method has higher performance and higher computation for decryption.